Technology Integration in Writing Instruction for Elementary School Student in Indonesia: A Systematic Literature Review - Rizkiah, Arni; Salim, Herli; Sopandi, Wahyu (International Conference on Elementary Education, 2025)
Writing instruction at the upper primary school level faces a variety of complex challenges, particularly in terms of improving student motivation, critical thinking skills, and the quality of their writing. Advances in digitaltechnology provide a strategic opportunity to enrich the writing learning process to make it more engaging, contextually relevant, and aligned with the characteristics of a generation that is familiar with the digital world. This study aims to systematically examine findings from previous studies related to the application of technology in writing instruction in upper elementary school. The approach used is a Systematic Literature Review (SLR), which thoroughly and structurally analyzes studies discussing the implementation of digital technology in upper elementary writing education. This method was chosen to ensure the review process is transparent, objective, and replicable. The SLR process includes the identification, selection, analysis, and synthesis of scholarly articlespublished between 2018 and 2024. Identification was carried out by searching academic articles from leading databases such as Scopus, Web of Science, ERIC, and Google Scholar. The findings reveal that the use oftechnologies such as digital storytelling, online collaboration platforms, learning management systems, and AI based applications can enhance student engagement, creativity, and narrative and expository writing skills. Additionally, technology integration encourages educators to develop innovative and flexible digital teaching methods. However, several obstacles were identified, including limited ICT facilities in schools, varying levels of teachers’ digital competence, and the need for ongoing training programs. The study concludes that integrating technology into upper elementary writing instruction holds great potential for improving writing literacy quality, provided it is supported by strong educational policies, adequate digital infrastructure, and enhanced teacher professionalism